UNCONDITIONAL ACCEPTANCE IN CRISIS WORK BASED ON THE LIVED EXPERIENCE OF MALAYSIAN COUNSELORS - Nur Husna Mohd Hafiz; Mohd Zaliridzal Zakaria; Wan Mohd Fazrul Azdi Wan Razali; Nurhafizah Mohd Sukor; Marina Munira Abdul Mutalib; Muhammed Fauzi Othman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Unconditional acceptance is one of the core attitudes in helping professionals to establish successful therapeutic relationships. Despite unconditional acceptance was accepted in most helping professional settings, it received less attention in academic scientific research due to scholars' disagreement regarding unconditional acceptance as a single separable construct from empathy and genuineness as proposed in person-centred therapy. The knowledge gap led to the implementation of this study, employing a qualitative method, specifically descriptive phenomenology. It aims to describe Malaysian counselors' experience exercising unconditional acceptance while encountering clients from various backgrounds. The thematic analysis revealed that unconditional acceptance encompasses acceptance of the client as a person, acceptance of the client's reality experience as part of them, and acceptance of the client's traumatic reaction. The findings indicate by years of experience, Malaysian counselors show high competency in practicing unconditional acceptance. It was found that unconditional acceptance requires counselors to have empathy, increasing their ability to comprehend the clients' situation and justify their emotional reactions. Counselors especially novice counselors need proper training and guidance to increase their ability to unconditionally accept their clients, their life experience, and their traumatic reactions. This study contributes to deepening the comprehension of implementing unconditional acceptance in counseling settings. It also provides new perspectives on improving the training curriculum for counselors in Malaysia, specifically in strengthening their skills in exercising unconditional acceptance and empathy attitudes.